Sistem Informasi Pengelolaan Klien untuk Meningkatkan Efisiensi Layanan - Damanik, Novianti (Jurnal Sistem Komputer (SISKOM), 2021)
This study aims to develop and implement a Client Management Information System to enhance service efficiency in business operations. The system is designed to streamline the management of client information, enabling better tracking, analysis, and communication. It integrates various functionalities such as client data storage, appointment scheduling, and automated reminders, which are crucial for maintaining strong client relationships and ensuring timely service delivery. By employing advanced data management techniques, the system ensures data accuracy and accessibility, thereby reducing the time and effort required for manual processes. The implementation of this system is expected to lead to significant improvements in operational efficiency, client satisfaction, and overall business performance. This paper discusses the design, development, and deployment phases of the system, as well as the challenges encountered and solutions adopted during the process. The results indicate that the Client Management Information System effectively addresses the limitations of traditional client management practices and offers a scalable solution for businesses aiming to enhance their service delivery capabilities.